Sharia Review of Mutual Funds Selling Agents: A Case Study of Ajaib Applications - Ahmad Fatoni; Roni Hidayat; Nining Nurhasanah (Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Kalijaga, 2022)
Capital market companies are currently developing, one of which is the spread of Islamic mutual funds which is facilitated by technological advances, namely the availability of platforms to make it easier for the users. PT. Takjub Teknologi Indonesia is an agent selling mutual fund securities, which carries the Ajaib application for mutual fund transactions. Companies that act as intermediaries for investors and investment managers. The formulation of the research problem is: What is the role and perspective of the sharia application of Ajaib as an agent selling mutual fund securities? This study aims to determine the role of the Ajaib application and review it in Sharia studies. The method used is a descriptive qualitative approach. This research resulted in several points as follows: 1). The role of the Ajaib application has the main task of marketing the securities of Islamic mutual funds to investment managers. Supported by the function of investor complaints and operating standards in writing, 2). Based on the Sharia review of the role of the Ajaib application, it fulfills the pillars and requirements of the samsarah contract, is following the sharia maqashid, and meets the existing fikhiyah rules, and in its application, this application meets muamalah etiquette.